2021
DOI: 10.1002/jnr.24816
|View full text |Cite
|
Sign up to set email alerts
|

How lung injury and therapeutic oxygen could alter white matter development

Abstract: Developmental brain injury describes a spectrum of neurological pathologies resulting from either antenatal or perinatal injury. This includes both cognitive and motor defects that affect patients for their entire lives. Developmental brain injury can be caused by a spectrum of conditions including stroke, perinatal hypoxia‐ischemia, and intracranial hemorrhage. Additional risk factors have been identified including very low birth weight, mechanical ventilation, and oxygen (O2) supplementation. In fact, infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…In this study, both FJC-positive cells and lung injury were found in the MTBI group mice, consistent with previous studies (22,29). MTBI attenuated the myelin injury associated with pneumonia, which may be via the expression and regulation of glucocorticoids.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, both FJC-positive cells and lung injury were found in the MTBI group mice, consistent with previous studies (22,29). MTBI attenuated the myelin injury associated with pneumonia, which may be via the expression and regulation of glucocorticoids.…”
Section: Discussionsupporting
confidence: 93%
“…Dettman and Dizon present an important review that has implications for all those who work in hypoxia‐ischemia in newborn brain in humans as well as in animal models (Dettman & Dizon, 2021). They trace the origin of the association between preterm chronic lung injury and white matter impairment to a central role of oxygen levels.…”
mentioning
confidence: 99%
“…Dettman and Dizon present an important review that has implications for all those who work in hypoxia-ischemia in newborn brain in humans as well as in animal models (Dettman & Dizon, 2021).…”
mentioning
confidence: 99%